HUBUNGAN ANTARA PERSEN LEMAK TUBUH DAN LINGKAR PINGGANG DENGAN HIPERTENSI PADA SISWA DI SMK HIDAYAH SEMARANG - Pratiwi, Ni Luh Gede Trisna; Maryanto, Sugeng; Purbowati (JURNAL GIZI DAN KESEHATAN, 2019)
Background: Obesity in adolescents can risk of hypertension. Percentage of body fat can describe the composition of the body. Waist circumference can be the option parameter to predict metabolicsyndrome. The objective of study is to find out the correlation between percentage of body fat and waist circumference with hypertension on students at Hidayah vocational school Semarang. Method: Research design was cross sectional. The population in this research was all eleventh and twelfth students in Hidayah vocational school Semarang with the samples of 97 people taken with purposive random sampling. Percentage of body fat was measured using BIA hand to foot,waist circumference was measured with metlineand blood pressure according to age, sexand height body. The data analysis used SPSS program. Bivariate analysis used chi-squaretest (Î±=0,05). Results: There is no correlation between percentage of body fat and hypertension on students at Hidayah vocational school Semarang (p=0,505) and there is no correlation between waist circumference and hypertension on students at Hidayah vocational school Semarang (p=0,108). Conclusion: There is no correlation between percentage of body fat and waist circumference and hypertension on students at Hidayah vocational school Semarang Abstrak : Latar Belakang: Obesitas pada remaja dapat menjadi risiko terjadinya hipertensi. Persen lemak tubuh dapat mencerminkan komposisi tubuh seseorang.Lingkar pinggang dapat menjadi parameter pilihan untuk memprediksi sindrom metabolik.Penelitian ini bertujuan untuk mengetahui hubungan antara persen lemak tubuh dan lingkar pinggang dengan hipertensi pada siswa di SMK Hidayah Semarang. Metode: Rancangan penelitian ini adalah cross sectional. Populasi penelitian adalah seluruh siswa kelas XI dan XII SMK Hidayah Semarang dengan jumlah sampel 85 orang diambil dengan teknik purposive random sampling. Persen lemak tubuh diukur dengan menggunakan BIA hand to foot, lingkar pinggang dengan metline dan tekanan darah diukur dengan membandingkan hasil dengan persentil tekanan darah menurut usia, jenis kelamin dan tinggi badan. Analisis data menggunakan program SPSS. Analisis bivariat menggunakan uji chisquare (Î± = 0,05). Hasil: Tidak ada hubungan antara persen lemak tubuh dengan hipertensi pada siswa di SMK Hidayah Semarang (p = 0,505) dan tidak ada hubungan antara lingkar pinggang dengan hipertensi pada siswa di SMK Hidayah Semarang (p=0,108). Simpulan: Tidak terdapat hubungan persen lemak tubuh dan lingkar pinggang dengan hipertensi pada siswa di SMK Hidayah Semarang.